Bee Venom Attenuates Experimental Autoimmune Encephalomyelitis through Direct Effets on CD4+CD25+FOXP3+ T Cells. (January 2013) - Lee, G.; Lee, H.; Park, S.; Jang, H.; Bae, H.
Multiple sclerosis (MS) is a chronic inflammatory disease of the central nervous system that leads to substantial disability through deficits of sensation and of motor, autonomic, and neuro-cognitive function. Many clinical and pathological features of experimental autoimmune encephalomyelitis (EAE) show close similarity to MS. Bee venom (BV) has been used in the practice of oriental medicine and evidence from the literature indicates that BV plays an anti-inflammatory or anti-nociceptive role against inflammatory reactions associated with arthritis and other inflammatory diseases. The purpose of the present study was to determine whether BV could suppress immune cell differentiation and infiltration into spinal cord on EAE mice commonly used as a model for MS. BV treatment increased the population of CD4 + CD25 + Foxp3 + T cells and inhibited CD4 + T-cell proliferation in vitro. In vivo, BV treatment increased the population of CD4 + CD25 + Foxp3 + T cells. Furthermore, BV administration reduced the severity of EAE while concurrently decreasing INF-γ producing CD4 + T cells, IL-17A producing CD4 + T cells and inflammatory cytokine production including INF-γ, IL-17A, TNF and IL-6. BV-treated animals exhibited less infiltration and preserved morphology compared to saline-treated animals. Interestingly, the therapeutic effects of BV on EAE disappeared when CD4 + CD25 + Foxp3 + T cells were depleted by using anti-CD25 antibody. Our research suggests that BV could be a potential therapeutic agent for antiinflammatory effects in an animal model of EAE.